Wasteland/Wetland Rewilding Water Systems in the Post Mining Landscape in the Nigel Region - Moll, Georgia Stephanie (University of the Witwatersrand, Johannesburg, 2024)
The Witwatersrand region, renowned for its historical mining activities, grapples with environmental degradation, particularly in its water systems. Mining operations have left a legacy of pollution through practices such as the disposal of mine waste in tailings located on or nearby rivers and wetlands, driven by convenience and insufficient regulation. This creates significant threats to the natural ecology and biodiversity of the region, such as acid mine drainage, which continues to impact water quality and ecosystem health long after mining activities have ceased, leading to the destruction of aquatic ecosystems, habitats, and breeding zones. Despite these challenges, research suggests that wetlands hold the key to addressing these challenges. Wetlands can be used to naturally filter wastewater, which can contain sediments and pollutants, improving water quality. They are also crucial in nutrient cycling, processing elements like nitrogen and phosphorus which are commonly found in mine runoff. The potential for wetlands to act as natural decontaminators highlights their importance in ecological repair and water security for the region. In areas where natural wetlands have been significantly damaged, constructed wetlands present a viable solution. These engineered systems can be strategically placed within damaged waterscapes to treat contaminated water through natural filtration. My thesis proposes an expansion of constructed wetlands into a multifunctional building typology designed to filter water as it flows through the structure. By incorporating various filtration processes and different types of constructed wetlands within the building, this concept aims to provide a pilot design that can be scaled and adapted for implementation in other contaminated sites throughout the region. The proposed building will serve multiple roles in filtration, showcasing a scalable solution for water decontamination and ecological restoration. By establishing this model, the project seeks to improve water security, restore ecological balance, and provide a blueprint for similar initiatives in other regions affected by mining related environmental degradation. Through this research, I will research the potential for wetlands—both natural and constructed—to serve as a foundation of environmental remediation and sustainability in the Witwatersrand region.
This research report is submitted in the partial fulfilment for the degree of Master of Architecture (Professional), to the Faculty of Engineering and Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: Wetland; Constructed Wetland; Re-wilding; Acid Mine Drainage; Ecological restoration; Hybrid Landscapes; Ecological resilience; WEF Nexus; Phytoremediation; UCTD; SDG-13: Climate action; SDG-11: Sustainable cities and communities